Turkish adaptation of Desire to Avoid Pregnancy Scale: A validity and reliability study - Dogan Yuksekol, Ozlem; Duman, Mesude; Timur Tashan, Sermin (Wiley, 2022)
Aim The purpose of the study was to adapt the Desire to Avoid Pregnancy Scale into Turkish and to study its validity and reliability. Methods The methodological study design was used. The study sample consisted of 510 nonpregnant women in a university hospital of a province in the east of Turkey between the dates of August 2019-February 2020. Personal information form and Turkish form of the scale were administered to women. The contraceptive intention scale was used as a parallel form. Results In the study, it was determined that the scale consisted of 14 items as a result of exploratory factor analysis. As a result of the item analysis, it was determined that the scale item total correlations were between r = 0.71 and 0.92. The Cronbach alpha coefficient of the scale was 0.97. The item-total correlation of the scale and parallel form reliability showed a high level of agreement. Conclusion It was determined that the Desire to Avoid Pregnancy Scale is a valid and reliable measurement tool for determining the wishes of Turkish women regarding pregnancy.
Keywords: Desire to Avoid Pregnancy Scale; pregnancy intention; pregnancy preferences; Turkish adaptation